Changes in forest bird abundance, community structure and composition following a hurricane in Sweden. Issue 11 (1st September 2019) - Chevalier, Mathieu; Lindström, Åke; Pärt, Tomas; Knape, Jonas
Abstract : The effect that extreme natural events have on biological diversity is relatively poorly known. We used a before–after control‐impact (BACI) design to analyze changes in bird abundances and communities following Hurricane Gudrun, which struck southern Sweden in January 2005, felling 75 million m 3 of forest and causing damage to 5% of forested areas (half a million hectares) in a few hours. We used recent measures of impact in combination with classical BACI contrasts to analyze bird count data from a monitoring program in Sweden. We investigated changes in the abundance of 17 species commonly found in forests, along with changes in species composition and functional structure of the bird community. In total, we considered 34 response variables and examined whether responses were immediate or long‐term. There was no evidence of a strong effect of the hurricane on the abundances of six species. Estimates of the effects on five species were too uncertain to draw inferences. We detected positive and negative effects of the hurricane on the abundances of the remaining six species, but the magnitude of effects often was small. Generally, the effects were in the expected direction: negative on birds associated with mature forest and positive on birds associated with open land or young forest. We found evidence of an increase in the proportion of species that nest on the ground and a decrease in the proportion of species that nest in cavities and trees. In contrast, the hurricane had no discernible effect on functional measures of diversity (richness, evenness or divergence), or on communities' reproductive or morphological characteristics. Our results suggest that the hurricane affected bird populations and communities, but the magnitude of effects was generally small.